Embozene loaded prostatic artery embolization - Abdul Rahim, Ezamin; Abdul Rahim, Ridzuan; Baseri Huddin, Azzam; Nik Ismail, Nik Azuan; Mohd Yakob, Mohd Naim (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Herein is a case report of a 70 years old man with a tenacious benign prostatic hyperplasia (BPH). The aim of this manuscript is to briefly discuss the usage and advantage of EmbozeneTM Microsphere in embolization of the prostate arteries in the treatment of failed medical and surgical therapy for BPH.